Selectivity in the cycloadditions of carbonyl ylides with glyoxylates: an approach to the zaragozic acids-squalestatins - Hodgson, D; Bailey, J; Villalonga-Barber, C; Drew, M; Harrison, T (2000)
Reaction of diazodiketoester 8 with glyoxylates in the presence of catalytic rhodium(n) acetate generates 6,8-dioxabicyclo[3.2.1]octanes 9 and 11 in good yield. Elaboration of 9 provides a suitable alcohol 25 for acid-catalysed rearrangement to give the 2,8-dioxabicyclo[3.2.1]octane skeleton 26 of the zaragozic acids-squalestatins. More substituted diazodiketoesters 36 and 40 also undergo highly regio- and diastereoselective cycloaddition with glyoxylates to give the cycloadducts 41,43 and 44. © The Royal Society of Chemistry 2000.